2022
DOI: 10.1021/acs.energyfuels.1c04246
|View full text |Cite
|
Sign up to set email alerts
|

Air Foams for Mobility Control and Subsurface Storage of Hydrogen in Porous Media: An Experimental Study

Abstract: This study initially explores and reports the feasibility of surfactant foams to increase the efficacy of hydrogen storage in porous media. This is an essential field of study, which aims to tackle a primary concern of the future hydrogen-based economy-hydrogen storage, which is essential for the supply of energy during periods of intermittent supply. For this, storage of hydrogen in porous media is explored wherein non-uniform front advance and superior gas mobility reduce storage efficacy. To mitigate this c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 62 publications
0
14
0
Order By: Relevance
“…The storage and extraction of H 2 requires displacing existing brine‐hydrocarbons and this will be affected by individual reservoir conditions at each site. In particular, the heterogeneity of the porous medium and the transport properties of the H 2 impact the injection and withdrawal cycles, and need to be accurately simulated to maximize storage and production efficiency (Chaturvedi et al., 2022; Mohammadmoradi & Kantzas, 2018). Accordingly, the behavior of injected hydrogen should be studied in terms of its mobility and multiphase flow properties (Iglauer et al., 2022; Razavifar et al., 2021; Sedev et al., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The storage and extraction of H 2 requires displacing existing brine‐hydrocarbons and this will be affected by individual reservoir conditions at each site. In particular, the heterogeneity of the porous medium and the transport properties of the H 2 impact the injection and withdrawal cycles, and need to be accurately simulated to maximize storage and production efficiency (Chaturvedi et al., 2022; Mohammadmoradi & Kantzas, 2018). Accordingly, the behavior of injected hydrogen should be studied in terms of its mobility and multiphase flow properties (Iglauer et al., 2022; Razavifar et al., 2021; Sedev et al., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…10): The IFT of H 2 reduces with depth whereas the H 2 viscosity increases, both of which in theory should augment the displacement of H 2 with water and reduce the S nwr [66,67]. However, increased S nwr with decreasing IFT and increasing viscosity has also been demonstrated [68] which may be due to a simultaneously increased likelihood of unstable displacement/non-uniform fronts [69,70] during both drainage and imbibition processes at decreasing IFT and increasing viscosity, based on the augmenting effect of both parameters on N C (Eq. ( 1)).…”
Section: Effect Of Pore Fluid Pressure and Hydrogen/brine Injection R...mentioning
confidence: 99%
“…10): The IFT of H2 reduces with depth whereas the H2 viscosity increases, both of which in theory should augment the displacement of H2 with water and reduce the Snwr 62,63 . However, increased Snwr with decreasing IFT and increasing viscosity has also been demonstrated 64 which may be due to a simultaneously increased likelihood of unstable displacement/ non-uniform fronts 10,65 during both drainage and imbibition processes at decreasing IFT and increasing viscosity, based on the augmenting effect of both parameters on NC (Eq. 1).…”
Section: Effect Of Pore Fluid Pressure and Hydrogen/brine Injection R...mentioning
confidence: 99%
“…It has been postulated that the low viscosity of H2 will cause the gas to travel swiftly, making it little suitable for displacing brine 10 and causing low H2 injectivity. In this work, we showed that from an injectivity and recovery perspective, untreated Clashach sandstone is suitable for underground H2 storage.…”
Section: Suitability Of the Clashach Sandstone For Hydrogen Storagementioning
confidence: 99%
See 1 more Smart Citation